Management of Subarachnoid–Pleural Fistula Following Anterior Transthoracic Approach for the Ossification of Posterior Longitudinal Ligament in the Thoracic Spine - Kanematsu, Ryo; Hanakita, Junya; Minami, Manabu; Takahashi, Toshiyuki (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2025)
Subarachnoid–pleural fistula (SAPF) is an abnormal communication between the subarachnoid and pleural spaces that can arise from blunt or penetrating trauma or as a complication of spinal surgery via the transthoracic approach. Uncontrolled cerebrospinal fluid (CSF) leakage after transthoracic spinal surgery could be more problematic than that after spinal surgery via the conventional posterior approach because of the negative pressure in the pleural cavity.The authors reported SAPF management using chest and lumbar drainage in five patients with several troublesome complications, such as intracranial subdural hematoma or severe respiratory dysfunction. Chest drainage was managed for 2 to 3 days by continuous low negative pressure, whereas lumbar spinal drainage was managed for 5 to 7 days, aiming at an output volume of 150 to 200 ml/day and higher than that of chest drainage. Additionally, when changes in the accumulated pleural fluid were seen by standing chest X-ray immediately before the operation and 1 month after the operation, the pleural effusions in four of the five patients were assimilated 1 month postoperatively.Compared with CSF management following standard posterior spinal surgery, management after the anterior transthoracic approach could be more troublesome because of the intrapleural negative pressure. When the chest and lumbar drainage are used, it is important to consider that overdrainage of CSF could potentially cause severe respiratory dysfunction and intracranial subdural hematoma.
Keywords: subarachnoid–pleural fistula; cerebrospinal fluid leakage; respiratory dysfunction; anterior transthoracic approach; thoracic ossification of posterior longitudinal ligament